A responsabilidade socioambiental das empresas mineradoras instaladas nos municípios de Pedra Branca do Amapari e Serra do Navio no Amapá: reflexão sobre a atividade mineradora e as práticas ambientais sustentáveis - Vilhena, Marlene dos Santos (2014)
This dissertation has as objective the characterization of mineral sector in the municipalities of Pedra Branca do Amapari and Serra do Navio both located in the State of Amapá, identifies the possible environmental impacts and socioenvironmental responsibility of mining companies installed in the municipalities mentioned above and, check the environmental impacts arising from the environmental management of mining enterprises, with a view on the contribution to sustainable development these municipalities and their environments. As referential framework, analyse the contemporary doctrine in order to enable the verification of the evolution of social and environmental development as a form of contribution for the discussion of effective guarantees of preservation of the environment and, in addition to different approaches how to prevent and repair from the possibility of application of principles applied to mining considering, as a the fundamental elements for the implementation of policies relating to sustainable mining. The importance of this study lies in fact the environment suffer consequences from human actions, having in wiew the harnessing and exploitation of natural resources. The study proposes a as aspect innovative/contribution is the economic production with the sustainability of mining companies where the actions within a socio-environmental compensation as an instrument "miner" in environmental licensing. It would be a variable (Institute of prior environmental compensation) that he should comply (art. 170, caput, VII of CF/88) in accordance with the legal device "prior environmental compensation" regulated by law No 9,985/2000. Where the entrepreneur in reason the potential activity and significantly detrimental that want to develop, which will cause environmental impacts. In addition to the constitutional definitions and infra-constitutional concerning to principles and fundamental values the system of preservation of the environment, the Brazilian legislation passed also counting with the National Environmental Policy, instituted by Federal Law No 6,938/81, of August 31, 1981. Which elected as important instrument environmental impact study (EIA) for the installation of any and all work or even activity that potentially could cause significant degradation of the environment in the face of those who wish to lawfully explore mineral resources